Contribuição da compreensão dos significados e respostas emocionais para os processos de projeto do design estratégico - Winkler, Camila Lucchesi (Universidade do Vale do Rio dos Sinos, 2013)
The current discussions about the meanings of consumption have become more constant, within this discussions, an space to explore the roles of objects in the society is perceived. By these arguments, objetcts are idealized as simbolic goods, and begin to add tangible and intangible elementos. Another factor that contributes to this discussion is the weight of this symbolic value as a way to evaluate values between objects. It’s possible to identify, the consumption experience as a way of combining symbolic values, resulting as a innovation of meaning before it’s consumers. This study is based on the search for new arguments which aim to conquer this markets needs that arise, stimulating aesthetic and sensory functions in the search for positive emotional responses within the consumption. Investigating the consumer experience in the jewelry market, willing to comprehend it’s meanings and emotional answers, this research conducted such investigation, having as references the knowledges of Experience Design and Emocional Design. The purpose of this investigation was to attribute these findings to a design process, guided by the visiono f Strategic Design. The motivation os this Project is based on the new needs os the market, uniting emocional stimulation in Design projects, seeking in this way innovations towards consumption theories.
Keywords: Luxury market and symbolic consumption; Emocional responses; Experience; Strategic design; Mercado de luxo e consumo simbólico; Respostas emocionais; Experiência; Design estratégico; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial